Predictive Model Approach to Enhancing Occupational Health Based on Safety Culture and Sustainable Technology in Environmental, Social, and Governance - Febiyani, Anastasia; Suhardi, Bambang; Laksono, Pringgo Widyo; Prastawa, Heru (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Occupational safety and health (OSH) is a key pillar in creating a productive and sustainable work environment, especially in the high-risk manufacturing sector. As global demands for Environmental, Social, and Governance (ESG) principles increase, the integration of safety culture and sustainable technology is an important strategy to strengthen the protection of workers' health while supporting industrial sustainability. Method: A quantitative approach was used by distributing questionnaires to 200 workers from various categories of manufacturing industries. The analysis used included correlation tests, multiple linear regression, and scenario simulations of technological improvements and recycling efficiency of personal protective equipment. Result: The main variables analyzed were discipline in wearing PPE, consistency, reward-punishment, and the application of wearable technology and environmentally friendly PPE. The regression results show that the discipline of using PPE is the most significant factor in shaping occupational safety culture (p = 0.001). Although the technology and reward variables are not statistically significant, the simulation shows that increased investment in safety technology can accelerate the growth of safety culture and indirectly strengthen occupational health protection.The implementation of sustainability principles, such as the use of environmentally friendly PPE materials and recycling programs, is also proven to reduce the impact of industrial waste and contribute to the Environmental aspect of ESG. Conclusion: While lowering the effect of industrial waste, the simulation reveals that higher investment in technology and recycling efficiency might hasten the change of safety culture from reactive to proactive. This study theoretically expands the safety culture approach to be more predictive and sustainable under the ESG framework, so improving its sustainability. Practically, these results give a basis for industrial policies to create OSH strategies compatible with digital transformation and world sustainability goals.